An Assessment of the River Water Quality Parameters: A case of Jamuna River (Journal of Environmental Science and Natural Resources, 2015)
River water quality is a key concern as it is used for drinking and domestic purpose, irrigation and aquatic life including fish and fisheries. The Jamuna River is one of the most prominent central rivers in Bangladesh as well as it represents the tapestries line of our riverine country. The river can play a vital role to contribute social economic structure of development as a developing country like Bangladesh. The study was conducted to assess the physical and chemical water quality parameters of Jamuna River. The water samples were collected in plastic container of 2 liters capacity from five different geographic locations along the river in 2012-2013 during both dry and wet season. And 25 numbers of samples were collected from surface and 2 feet below from the surface of water at different selective sampling points. A number of physiochemical water quality parameters including Temperature, pH, EC, TDS, DO, BOD, COD, Nitrate (NO2- and NO3-), Ammonia, Sulphates, Chlorides, and Calcium were measured in laboratory base analysis. The mean value of such respective parameters in both season were compared with the water quality standards as set by the EQS guideline, ADB, and the guideline of Department of Environment (DoE) in Bangladesh.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22179 J. Environ. Sci. & Natural Resources, 7(1): 249-256 2014